Monotone Equilibrium in Multi-Unit Auctions - McAdams, David (Review of Economic Studies, 2006)
In two-sided multi-unit auctions having a variety of payment rules, including uniform-price and discriminatory auctions, a monotone pure-strategy equilibrium (MPSE) exists when bidders are risk neutral with independent multi-dimensional types and interdependent values. In fact, all mixed-strategy equilibria are ex post allocation and interim expected payment equivalent to MPSE. Thus, for standard expected surplus/revenue analysis, there is no loss restricting attention to monotone strategies. Copyright 2006, Wiley-Blackwell.